Analysis of Financing of Innovative Activities of Agroclusters (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
this article analyzes the financing of innovative activities of agroclusters, including the creation of a modern organizational structure of the cluster and a system of financial and economic relations, ensuring the use of various resources and technologies, the possibility of attracting qualified personnel, as well as the development of practical proposals and recommendations for financing the activities of agroclusters.